The American Short Story Cycle - Smith, Jennifer J. (Edinburgh University Press, 2017)
The American Short Story Cycle shows the roots of modernism and postmodernism winds through the short story cycle.Reviewers ranging from the The New York Times to Amazon do not know what to call books like Jennifer Egan's A Visit from the Goon Squad or Jhumpa Lahiri's Unaccustomed Earth. Why do such popular and acclaimed books spark debates about what they are and how they should be read? The American Short Story Cycle provides a history of this genre that has been hiding in plain sight. Dating back to the early nineteenth century and proliferating to the present, the short story cycle has been wildly popular both in the US and around the world. Stories in a cycle, which can be read singly but mean more together, reflect the individualism and pluralism that shape modern experience. This book gives a name and theory to the genre that has fostered the aesthetics of fragmentation and recurrence that characterize fiction today.